Isolation of Listeria monocytogenes from cerebrospinal fluid - Takeuchi, Chifumi (1974)
From November 1973 to June 1974 a systematic research on 1 008 samples of feculent and purulent cerebral spinal fluid was carried out at the Instituto Adolfo Lutz. Such study was developed to disclose the extension of the role of Listeria Monocitogenes in thís type of infection. As a general result it was demonstrated that no other micro-organisms took part in the process, All samples were incubated from 4 samples only. In one of these samples isolation was made at 4ºC; in two other samples at 15°C and in the 4th sample isolation was obtained at both temperatures. In almost all cases bacteria was isolated after one week incubation period under low temperature.